The World health report : health systems financing : the path to universal coverage. (WHO GenevaCH, 2010)
Outlines how countries can modify their financing systems to move more quickly towards universal coverage and how to sustain those achievements. Synthesises new research and lessons learnt from experience into a set of possible actions that countries at all stages of development can consider and adapt to their own needs.
Keywords: HEALTH FINANCING